2018
DOI: 10.1371/journal.pone.0199742
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of superheated steam hydrolyzed oligo((R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate) and characteristics of its blend with poly(L-lactic acid) for biomaterial applications

Abstract: In order to clarify the in vitro cytotoxicity effect of superheated steam (SHS) treated poly((R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate) (PHBHHx) for biomaterial applications, SHS-treated PHBHHx oligoester samples: P(HB-co-6%-HHx) and P(HB-co-11%-HHx) with low and high percentages of unsaturated chain ends were evaluated for their cytotoxicity effects toward the growth of mouse fibroblast cell line NIH 3T3. From the results obtained after 24 and 48 h of the growth test, the SHS-treated PHBHHx oligoesters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For these reasons, we have carried out direct compatibility analysis, seeding the (MC3T3-E1) directly on our materials ( Figure 7 B,C). Cell proliferation ability on surfaces based on PHAs was evaluated already in various cell models [ 25 , 26 , 27 , 31 , 32 , 33 , 34 , 59 ]. Our study shows increased viability along with the time of cell incubation on the surface of TCP/P(3HO) composites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, we have carried out direct compatibility analysis, seeding the (MC3T3-E1) directly on our materials ( Figure 7 B,C). Cell proliferation ability on surfaces based on PHAs was evaluated already in various cell models [ 25 , 26 , 27 , 31 , 32 , 33 , 34 , 59 ]. Our study shows increased viability along with the time of cell incubation on the surface of TCP/P(3HO) composites.…”
Section: Resultsmentioning
confidence: 99%
“…The use of a low molecular weight matrix is also beneficial in terms of increasing the degradation rate of the polymeric material as shown in [ 64 ]. Rajaratanam et al reported that the use of (P(3HB)-co-(3HHx)) oligoesters favours the process of the degradation of threads made of these materials [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P(4HB) homopolymer has been discovered to be a promising material for absorbable sutures because its breakdown products are far less acidic than poly(glycolic acid) (PGA) or polycaprolactone (PCL), and it breaks down faster than PCL, PLLA and other PHAs, such as PHB [ 97 ]. By 2007, two other PHA-based suture materials–Phantom Fiber TM (Tornier Co., Bloomington, ID, USA) and MonoMax ® (Braun Surgical Co., Hessen, Germany)—had been FDA-approved and were prepared using P(4HB) [ 91 ].…”
Section: Biomedical Applications Of Phamentioning
confidence: 99%
“…However, thermal, mechanical and chemical properties of PHB homopolymer by itself are somewhat limited for wider applications. To improve the properties of PHB, many attempts have been studied by copolymerization [2,8,9,10,11,12] and blending [13,14,15] with the other polymers. The PHB-based copolymers have been extensively studied using infrared (IR) [16,17,18,19] and Raman [8,10,20] spectroscopies, wide-angle X-ray scattering (WAXS) [11,20,21], X-ray diffraction (XRD) [22,23], differential scanning calorimetry (DSC) [24,25], and so on.…”
Section: Introductionmentioning
confidence: 99%